Marriage Registration Assistance According to Law No. 1 of 1974 on Marriage - Sobardo Hamonangan; Mulyadi, Dudi; Kadir Katjong; Supriyanto Hadi; Frans Reumi (Jurnal Insan Pengabdian Indonesia, 2024)
The title of this community service program is "Marriage Registration Assistance According to Law No. 1 of 1974 on Marriage," which was held on August 25, 2024, at the Sidang Jemaat Allah Efesus Church in Jayapura Regency, with 28 (twenty-eight) congregants in attendance. The activity utilized counseling and interactive discussion methods to provide a comprehensive understanding of the importance of official marriage registration according to the law. Participants were given a step-by-step guide on the marriage registration process and informed about the legal rights obtained after the marriage is registered. The outcome was an increased awareness among the congregants about the significance of official marriage registration, with several participants expressing interest in registering their marriages in accordance with applicable legal provisions.